2010
DOI: 10.5630/jans.30.3_13
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Pre-operative Gastrointestinal Cancer Patients Who Utilized Their Health Literacy, Starting from Initial Detection of Symptoms to Cancer Diagnosis

Abstract: The purpose of this study is to investigate the mechanics and processes by which gastrointestinal cancer GIC patients utilized their health literacy awareness, starting from initial detection of symptoms to cancer diagnosis. Method Participant observation and semi-structured interview data from 10 pre-operative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Thus, our study is the first to establish an association between low HL and having a long PCI. A few studies have found that HL may influence mechanisms with regard to help-seeking behaviour (the patient interval) (McEwan et al, 2014;Nakagami & Akashi, 2010). The present study adds to this body of knowledge by indicating that the patients' health literacy may also influence the diagnostic process after initial help-seeking in general practice.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, our study is the first to establish an association between low HL and having a long PCI. A few studies have found that HL may influence mechanisms with regard to help-seeking behaviour (the patient interval) (McEwan et al, 2014;Nakagami & Akashi, 2010). The present study adds to this body of knowledge by indicating that the patients' health literacy may also influence the diagnostic process after initial help-seeking in general practice.…”
Section: Discussionsupporting
confidence: 51%
“…total interval) was 8.82 months ( SD ± 11.41, range 1–48 months). The two qualitative studies did not seek to quantify the time from symptom onset to diagnosis, although patients’ narratives were used to demonstrate how the time to diagnosis may be influenced (McEwan et al, ; Nakagami & Akashi, ). Participants included in the qualitative study by McEwan et al were sampled from a prior quantitative study assessing the time to diagnosis in breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 summarises the methodological quality of the studies, which ranged from poor to adequate. Study details such as setting, sampling strategy and exclusion criteria were poorly described, with only one study fully describing the participant inclusion criteria (Nakagami & Akashi, 2010). The small sample sizes impacted the analysis, with Nakagami and Akashi unable to reach theoretical saturation based on the grounded theory approach used (Strauss & Corbin, 1998).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively little information exists about how patient understanding and health literacy affect the timely diagnosis of symptomatic cancer, with some indication that processes of monitoring and evaluating symptoms may affect the time to diagnosis. 13 , 14 Cancer, being one of the most complex and challenging diseases, presents unique difficulties for patients in comprehending diagnostic pathways and treatment options. Studies have shown that patients often face significant challenges in understanding cancer‐related information, associated with suboptimal care.…”
Section: Introductionmentioning
confidence: 99%